Antecedents and Consequences of Shared Vision Dissemination Quality: Evidence from Public and Private Universities in Indonesia and Malaysia - Anggia Sari Lubis; Khalid Abdul Wahid; Mohd Nasir Ismail; Debbi Chyntia Ovami (CV. RADJA PUBLIKA, 2026)
This study examines how organizational commitment, transformational leadership, and readiness for change influence shared vision dissemination quality and, in turn, employee performance in higher education institutions. A cross-sectional survey was administered to 200 lecturers and educational staff from public and private universities in Indonesia and Malaysia. Data were analyzed using PLS-SEM with SmartPLS 4.0. The results indicate that organizational commitment, transformational leadership, and readiness for change significantly enhance shared vision dissemination quality, which strongly predicts employee performance. Transformational leadership emerges as the strongest predictor of shared vision dissemination quality. These findings highlight the strategic role of effective vision dissemination in strengthening organizational learning and performance in universities. The study contributes by integrating insights from the Theory of Reasoned Action, Learning Organization Theory, and Cognitive Learning Theory to conceptualize shared vision dissemination quality and explain its antecedents and outcomes.